Navigating the Obstacles and Complexities of ICT Integration in Pakistan's Education Sector - Sain, Zohaib Hassan; Vasudewan, Asokan; Lawal, Uthman Shehu (Formosa Journal of Science and Technology, 2024)
This study analyses the challenges associated with incorporating Information and Communication Technologies (ICTs) into secondary education in Pakistan, with a particular emphasis on the city of Lahore. This aims to highlight the primary challenges faced at the institutional, teacher, and student levels, as well as the potential components that might assist in overcoming these challenges. The research uses a sequential mixed-method technique, in which the interview material is exposed to qualitative analysis, and the survey data are reviewed statistically. The results indicate that participants generally have a favourable view regarding incorporating information and communication technologies (ICTs) into the learning process. However, even though administrators and Information and Communication Technology coordinators are aware of several challenges and potential elements that might facilitate the incorporation of ICT, there is a need for additional viewpoints to be shared between staff and students about particular difficulties. The study outlines the problems and the topics of dispute about the obstacles that stand in the way of integrating ICT.